2019
DOI: 10.2478/foli-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Nexus Between Government Expenditure and Inflation in Nigeria

Abstract: Research Background: The on-going debate concerning the exact relationship that exists between inflation and government expenditure especially in the long and short run prompted this research. Purpose: The study assesses the relationship between government expenditure and inflation in Nigeria. Apart from government expenditure and inflation rate, other variables such as exchange rate and money supply are included to ensure a robust model. Research Methodology: Secondary data from 1980 to 2017 were collected an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 8 publications
1
0
0
Order By: Relevance
“…The persistently high level of public spending leads to an increase in the price level, which causes inflation. This result is similar to Keynes (1937), Kwon et al (2006), Attari and Javed (2013), Nguyen (2015), and Oyerinde (2019). The general price level will increase when implementing fiscal policy and monetary policy to boost economic growth and create jobs for the people.…”
Section: Empirical Results and Discussionsupporting
confidence: 67%
“…The persistently high level of public spending leads to an increase in the price level, which causes inflation. This result is similar to Keynes (1937), Kwon et al (2006), Attari and Javed (2013), Nguyen (2015), and Oyerinde (2019). The general price level will increase when implementing fiscal policy and monetary policy to boost economic growth and create jobs for the people.…”
Section: Empirical Results and Discussionsupporting
confidence: 67%
“…Short run results showed that budget deficit and government expenditure has positive impact, but tax revenue and external debt has negative impact on inflation rate. Oyerinde (2019) examined the relationship between government expenditure and inflation in Nigeria using data from 1980 to 2017. Johansen Cointegration analysis and vector error correction model results showed that apart from the bi-directional relationship that exists between the variables, there exists a strong relationship between government expenditure and Review of empirical literature has shown that most literature did not disaggregate government expenditure into recurrent and capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yazara göre kamu harcamalarının enflasyon üzerindeki etkisi toplam talep artışı kanalıyla gerçekleşmekteyken GSYİH artışı ise enflasyon oranlarının düşmesine katkı sunmaktadır. Oyerinde (2019), Nijerya'da kamu harcamalarıyla enflasyon arasındaki kısa ve uzun dönemli ilişkiyi incelemiştir. Çalışmanın bulguları, hem kısa hem de uzun dönemde kamu harcamalarının enflasyonun bir nedeni olduğunu dahası bu etkinin karşılıklı olduğunu göstermektedir.…”
Section: Literatürunclassified
“…(2008),Nguyen (2015),Mehrara vd. (2016) veOyerinde (2019) gibi çalışmalardan elde edilen sonuçlar ile benzerlik göstermekte ve temel olarak ekonomik teorilere ve bazı ampirik bulgulara göre şu şekilde açıklanmaktadır: Öncelikle Keynesyen okul tarafından ileri sürülen toplam talep ve arz teorilerine göre, kamu harcamalarındaki artışlar, kamunun tüketim ve yatırımlarındaki artışın bir sonucu olarak toplam talep artışına sebep olacak ve fiyatlar genel seviyesi üzerinde yukarı yönlü bir baskı oluşturacaktır. Ancak bazı çalışmalarda ise bu durumun yalnızca kısa dönemde oluşabileceği savunulmaktadır.…”
unclassified